Islamic Students' Attitudes and Motivation toward Learning English: Indonesian Context - Rejeki, Sri (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2023)
This study investigates the attitudes and motivation of Islamic students toward learning English at several state Islamic universities in Indonesia. This study uses a quantitative research methodology with a survey design. Data were collected from 123 Islamic students from twelve universities across five major Indonesian islands. The findings show that Islamic students have a positive attitude toward learning English, both in terms of cognitive, affective, and conative. Students also have positive motivation from intrinsic and extrinsic components. Technological developments such as the internet and social media help students increase their motivation to learn English, especially in spreading Islamic teachings globally. However, this research is still being investigated in general. It is recommended for future researchers to be able to explore students' attitudes and motivation from other factors such as gender, grades, and family background to find out attitudes and motivation in more depth.